2018
DOI: 10.1136/oemed-2018-105077
|View full text |Cite
|
Sign up to set email alerts
|

Effects of office workstation type on physical activity and stress

Abstract: ObjectiveOffice environments have been causally linked to workplace-related illnesses and stress, yet little is known about how office workstation type is linked to objective metrics of physical activity and stress. We aimed to explore these associations among office workers in US federal office buildings.MethodsWe conducted a wearable, sensor-based, observational study of 231 workers in four office buildings. Outcome variables included workers’ physiological stress response, physical activity and perceived st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 32 publications
3
60
1
1
Order By: Relevance
“…In this regard, literature has shown that the percentage of office employees classified as PA fluctuators ranges from 16% to 69% [10,13], and this trend is increasing rapidly [11]. Such insufficient PA patterns are associated with negative health outcomes among office employees, including cardiovascular diseases, musculoskeletal disorders and other chronic diseases [14,15]. In order to support fluctuators to engage in regular PA and receive health benefits, understanding fluctuators' PA behavior and their related psychosocial features is a crucial prerequisite.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, literature has shown that the percentage of office employees classified as PA fluctuators ranges from 16% to 69% [10,13], and this trend is increasing rapidly [11]. Such insufficient PA patterns are associated with negative health outcomes among office employees, including cardiovascular diseases, musculoskeletal disorders and other chronic diseases [14,15]. In order to support fluctuators to engage in regular PA and receive health benefits, understanding fluctuators' PA behavior and their related psychosocial features is a crucial prerequisite.…”
Section: Introductionmentioning
confidence: 99%
“…We assessed a number of physical activity metrics at the office including activity postures (sitting, standing, walking, lying), postural transitions (sit‐to‐stand, sit‐to‐lie, stand‐to‐walk), total number of taken steps, average of unbroken walking bouts in seconds (average duration of all recorded continuous walking bouts with a minimum of three consecutive steps), and average physical activity level (defined by the intensity of the acceleration magnitude [mG] per second). This last measure is our main method of capturing overall physical activity as it can be connected to clinical definitions for sedentary behavior and was utilized in previous work by our Wellbuilt for Wellbeing project . To capture physical activity outside of the office, we estimated the percentage of activity behavior (eg, sedentary, light, and moderate‐to‐vigorous activities) using a validated algorithm tailored for this study …”
Section: Methodsmentioning
confidence: 99%
“…This last measure is our main method of capturing overall physical activity as it can be connected to clinical definitions for sedentary behavior and was utilized in previous work by our Wellbuilt for Wellbeing project. 30 To capture physical activity outside of the office, we estimated the percentage of activity behavior (eg, sedentary, light, and moderate-tovigorous activities) using a validated algorithm tailored for this study. 31…”
Section: Physical Activity Measurementmentioning
confidence: 99%
“…The PAMSys TM sensor contains a 3-axis accelerometer (sampling frequency of 50 Hz) and built-in memory for recording long-term data. The description of methods to extract metrics of interest was described in details in our previous studies [38][39][40][41][42].…”
Section: Sensor-derived Monitoring Of Mobility Performancementioning
confidence: 99%